FITM2 deficiency results in ER lipid accumulation, ER stress, and reduced apolipoprotein B lipidation and VLDL triglyceride secretion in vitro and in mouse liver - Haizhen Wang; Cyrus Nikain; Konstantinos I. Fortounas; Jaume Amengual; Ozlem Tufanli; Maxwell La Forest; Yong Yu; Meng C. Wang; Russell Watts; Richard Lehner; Yunping Qiu; Min Cai; et al. (Elsevier, 2024)
Objective: Triglycerides (TGs) associate with apolipoprotein B100 (apoB100) to form very low density lipoproteins (VLDLs) in the liver. The repertoire of factors that facilitate this association is incompletely understood. FITM2, an integral endoplasmic reticulum (ER) protein, was originally discovered as a factor participating in cytosolic lipid droplet (LD) biogenesis in tissues that do not form VLDL. We hypothesized that in the liver, in addition to promoting cytosolic LD formation, FITM2 would also transfer TG from its site of synthesis in the ER membrane to nascent VLDL particles within the ER lumen. Methods: Experiments were conducted using a rat hepatic cell line (McArdle-RH7777, or McA cells), an established model of mammalian lipoprotein metabolism, and mice. FITM2 expression was reduced using siRNA in cells and by liver specific cre-recombinase mediated deletion of the Fitm2 gene in mice. Effects of FITM2 deficiency on VLDL assembly and secretion in vitro and in vivo were measured by multiple methods, including density gradient ultracentrifugation, chromatography, mass spectrometry, stimulated Raman scattering (SRS) microscopy, sub-cellular fractionation, immunoprecipitation, immunofluorescence, and electron microscopy. Main findings: 1) FITM2-deficient hepatic cells in vitro and in vivo secrete TG-depleted VLDL particles, but the number of particles is unchanged compared to controls; 2) FITM2 deficiency in mice on a high fat diet (HFD) results in decreased plasma TG levels. The number of apoB100-containing lipoproteins remains similar, but shift from VLDL to low density lipoprotein (LDL) density; 3) Both in vitro and in vivo, when TG synthesis is stimulated and FITM2 is deficient, TG accumulates in the ER, and despite its availability this pool is unable to fully lipidate apoB100 particles; 4) FITM2 deficiency disrupts ER morphology and results in ER stress. Conclusion: The results suggest that FITM2 contributes to VLDL lipidation, especially when newly synthesized hepatic TG is in abundance. In addition to its fundamental importance in VLDL assembly, the results also suggest that under dysmetabolic conditions, FITM2 may be an important factor in the partitioning of TG between cytosolic LDs and VLDL particles.